Appropriate Community Participation Process for Dispute Resolution in Kon Watershed Management, Nan Province, Northern Thailand - Rattana, Kitichai; Niyom, Wicha (วารสารวนศาสตร์ไทย, 2022)
The research aims to develop Appropriate Community Participation Process (ACPP) for the dispute resolution in Kon watershed management, Nan Province. The Participatory Action Research (PAR), which emphasizes the establishment of a Core Planning Team (CPT) and the People’s Party (PP), were used for the research methodology. The PAR provides a mechanism to build a multi-stakeholder partnership and identify land utilization problems in watershed regions. The results showed that community empowerment for the protection and conservation zone and the utilization zone were 72.89 % (163.02 km2) and 27.11% (60.64 km2), respectively. The planning and management for natural resource in the watershed region emphasizes: zoning for land utilization, forest and headwater restoration; forest fire protection, water resource development; and potential community career promotion. In addition, a pilot project utilizing Geographic Information System (GIS) to provide flashflood and landslide warnings drew the attention of the CPT of Amphur Chiang Klang to yearn for more knowledge and skills, and finally led the Municipality for the continual actions. The precision and accuracy testing of ACPP towards the CPT and PP process can solved conflict in Kon watershed. It took almost three years for the community to accept the fact that the ACPP was capable of resolving conflicts in Kon watershed. Nonetheless, socio-economic and culture characteristics as well as foregoing conflicts among the watershed community have limited the application of ACPP. As a result, should the ACPP be started at a small-scale watershed with the consideration of physical and socio-economic characteristics in harmony. It is advisable that multi-stakeholders in the watershed area must be clearly defined and any ACPP action should be incorporated to the conduct of the study. This would enccourage confidence among the people towards the researcher. Finally, the government has important role in proceeding ACPP adoption for watershed management, as it has the potential to reduce conflicts in other watershed regions within Thailand. Key words: community participation, dispute resolution, watershed management